Analysis of Time Series Gene Expression and DNA Methylation Reveals the Molecular Features of Myocardial Infarction Progression - Han, Yuru; Duan, Baoyu; Wu, Jing; Zheng, Yanjun; Gu, Yinchen; Cai, Xiaomeng; Lu, Changlian; Wu, Xubo; Li, Yanfei; Gu, Xuefeng (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI) is one of the most deadly diseases in the world, and the changes at the molecular level after MI was unclear. This study aims to explore the key genes and epigenetic characteristics affecting MI progression using RNA sequencing data and methylated DNA immunoprecipitation sequencing data. Analysis based on a single point in time, the immune response and apoptosis pathways are essential pathways at each point in time. Analysis was based on time series data, the expression of 1012 genes was specifically downregulated, and these genes were associated with energy metabolism. The expression of 5806 genes was specifically upregulated, and these genes were associated with immune regulation, inflammation and apoptosis. Transcription factors and corresponding target genes were identified in the genes involved in apoptosis and inflammation. 17 drugs were screened out that target these transcription factors, such as HMPL-004, mesalazine, and sulfasalazine. Analysis based on MeDIP-seq combined with RNA-seq methodology, focused on methylation at the promoter region. GO revealed that the downregulated genes with hypermethylation at 72 h were enriched in biological processes such as cell-cell adhesion, regulation of the apoptotic signalling pathway and regulation of angiogenesis. In addition, the upregulated genes with hypomethylation at 72 h were enriched in biological processes, such as cardiac muscle contraction and heart contraction. Among these genes, the Tnni3 gene was also present in the downregulated model. Hypermethylation of Tnni3 at 72 hours after MI may be an important cause of exacerbation of MI.